Estrategia Didáctica Basada En La Lúdica Para La Adquisición De Competencias Financieras En Estudiantes De La Licenciatura En Administración - Armando Sánchez-Macías; Virginia Azuara-Pugliese; Ma Lourdes Martínez-Cerda (European Scientific Journal, ESJ, 2018)
Financial competencies are about knowledge and understanding of both, financial concepts and financial risks, as well as the confidence to put them into practice. Ludic didactic strategies can be oriented towards knowledge acquisition of such skills. This paper aims to describe the impact of the use of a ludic didactic strategy to acquire financial competencies in undergraduate Management students in the CARAO –UASLP. This study is correlational, longitudinal with a quantitative approach that includes a quasiexperiment. A previous financial competencies diagnosis was performed as well as a latter one in an experimental and control group using a test and a survey. All of the students allocated in the second semester were tested and surveyed. The intervention done only in the experimental group was through a board game called “Cashflow 101” during a period of time of two months. The test outcomes show that most students require financial education and according to the survey approximately 70% has never used financial services altogether. Nevertheless, a relationship was found among financial competencies and various aspects of social contexts, such as owning a house or a car, which seem to increase the chances of having used financial services. Overall, it is clear that the use of the board game serves as a ludic tool for developing financial skills in a ludic form.